Outcomes for young carers: public and third sector provision in Wales, UK - Enid Vanessa Webb (2016)
Young carers are those under the age of 18 who provide unpaid care for an adult or child in need of support. The 2011 Census estimated that there were over 11,000 in Wales (Office for National Statistics, 2013) but research suggests that there are many more unidentified. They can be adversely affected by their caring role yet there is a weak evidence base for services and predictors of outcomes. This thesis aimed to explore service provision and outcomes for young carers. It also aimed to identify associations between outcomes and biographical characteristics or caring factors. To meet the aims of the study a mixed methods approach was adopted although the quantitative approach dominated (see section 6.1 for more details). This included a review of literature and two sequential data collection phases.Phase 1 aimed to map and evaluate extent of existing provision for young carers in Wales. Be-spoke questionnaires were completed by representative organisations (n=22) drawn from the two main service networks: Social Services (n = 12: 55% of all local authorities in Wales) and Young Carers Projects (n = 10).In response to Research Question about the development of provision, the results of Phase 1 indicated that the Projects, mostly delivered by the third sector, had developed as specialist support for young carers. There was common understanding and a high degree of co-operation between the statutory service and the Projects with some delegation of statutory functions. The stated objectives varied between Projects as did the evaluation of outcomes between sectors and between organisations and the data lacked comparability. Both statutory and third sector services suffered from lack of resources and the future of the Projects was far from stable.Phase 2 had two Research Aims. The first was to examine factors which influenced outcomes for young carers. The second was to evaluate the relative importance of factors. Published measures of4Educational Attainment (British Ability Scales), Emotional Literacy (SEMERC) and caring responsibilities (MACA-18) were administered alongside a be-spoke structured questionnaire to young carers (n = 62) from Projects (n=10) across Mid and South Wales. From the data sources, four outcome indices were calculated for the areas of Education, Emotional Literacy, Health and Social Capital. A Composite outcome index was also calculated.The results indicated that, on average, young carers’ Educational Attainment and Emotional Literacy were lower than those for age-matched peers in the general population. A worrying proportion had little or no social activities and personal hobbies outside school hours and outside time spent caring, with a consequent impact on their ability to acquire social capital. There appeared to be strong correlations between outcomes in Emotional Literacy, Health and Social Capital. Counter-intuitively some factors such as being a sole carer or entitlement to free school meals were not associated with any outcome indices.The strongest predictor of Composite outcomes was the quality of family relationships. Young carers who live in a family with poor quality of relationships are 46 times more likely to experience poor outcomes. Similarly, the higher the level of household responsibilities or emotional care, the more likely they are to experience adverse outcomes as reflected in their Composite index.The general findings suggest that a cross-cutting approach to policy on young carers requires monitoring in all policy areas. Since current provision leans heavily on the Projects, their funding needs to be reviewed at a strategic level. The large number of young carers still unidentified indicates that the capacity and effectiveness of the services need to be reviewed with other models of service considered. It is hoped that these findings will inform future policy formation and service planning.